Theoretical Study of Small Niobium Sulphide Clusters, $Nb_nS_m (m,n=1, 2)$ (Journal of Atomic and Molecular Sciences, 2014)
Clusters are well known for their extensive applications in various fields astheir properties are quite different from their bulk analog. In the present study, wehave investigated various conformers of $Nb_nS_m (n,m=1, 2)$ clusters in their neutralas well as anionic and cationic states. Their stabilities are discussed by calculatingbinding energies per atom and fragmentation energies against dissociation to $S$ atom.The electronic properties are also explored for all the species.
Keywords: atomic clusters; stability; density functional theory (DFT).